Analysis of Deviant Sexual Behavior (Same-Same Marriage) from a Legal Sociology Perspective - Tondi Rivaldi Munthe; Risdalina Risdalina; Maya Jannah (CV. AFDIFAL MAJU BERKAH, 2025)
This research is normative legal research that discusses sexual deviant behavior in same-sex marriages from the perspective of legal sociology in Indonesia. Based on Law Number 1 of 1974 concerning Marriage, marriage in Indonesia is defined as an inner and outer bond between a man and a woman as husband and wife to form a happy and eternal family based on the belief in the Almighty God. Therefore, same-sex marriage is not legally recognized in Indonesia. Article 1 Law no. 1 of 1974 confirms that a valid marriage is between a man and a woman, so same-sex relationships are not considered a valid marriage. Even if same-sex marriage is legally recognized abroad, Indonesia still does not recognize it as a valid marriage. From a legal sociology perspective, factors that influence the occurrence of deviant sexual behavior (same-sex marriage) include: education and knowledge, environment, family, And culture.